The results the dangerous geological and technogenic processes monitoring on the territory of Perm region in 2017-2018 - Lavrova, N.V.; Kadebskaya, O.I.; Bogomaz, M.V. (Perm Federal Research Centre Journal, 2018)
The results of the examination of dangerous geological processes on the territory of the Perm region from January 2017 to June 2018 are considered: failures, cracking, disappearing lakes. The formation of surface karst forms is condutioned by natural and anthropogenic factors. There have been increasing number of karst failures recently as the result of human activities. Information is given on the elimination of failures.